Safety and efficacy of insulin degludec/liraglutide (IDegLira) added to sulphonylurea alone or to sulphonylurea and metformin in insulin‐naïve people with Type 2 diabetes: the DUAL IV trial. Issue 2 (7th October 2016) - Rodbard, H. W.; Bode, B. W.; Harris, S. B.; Rose, L.; Lehmann, L.; Jarlov, H.; Thurman, J.
Abstract: Aim: To investigate the safety and efficacy of insulin degludec/liraglutide (IDegLira), a novel combination product, as add‐on therapy for people with Type 2 diabetes uncontrolled on sulphonylurea therapy. Methods: In this 26‐week, double‐blind trial, adults with Type 2 diabetes [HbA1c 53–75 mmol/mol (7.0–9.0%)] were randomized to IDegLira ( n = 289) or placebo ( n = 146) as add‐on to pre‐trial sulphonylurea ± metformin, titrating to a fasting glycaemic target of 4.0–6.0 mmol/l. Treatment initiation was at 10 dose steps, and maximum dose was 50 dose steps (50 units insulin degludec/1.8 mg liraglutide). Results: The mean HbA1c decreased from 63 mmol/mol (7.9%) to 46 mmol/mol (6.4%) with IDegLira and to 57 mmol/mol (7.4%) with placebo [estimated treatment difference –11 mmol/mol (95% CI –13; –10) or –1.02% (95% CI –1.18; –0.87); P < 0.001]. The HbA1c target of 53 mmol/mol (<7%) was achieved by 79.2% of participants in the IDegLira group vs 28.8% in the placebo group [estimated odds ratio 11.95 (95% CI 7.22; 19.77); P < 0.001]. Mean weight change was +0.5 kg with IDegLira vs –1.0 kg with placebo [estimated treatment difference 1.48 kg (95% CI 0.90; 2.06); P < 0.001]. Confirmed hypoglycaemia occurred in 41.7 and 17.1% of IDegLira‐ and placebo‐treated participants, respectively, with rates of 3.5 vs 1.4 events/patient‐years of exposure [estimated rate ratio 3.74 (95% CI 2.28; 6.13); P < 0.001]. IDegLira was generally well tolerated. The rates of serious adverse events were 20.3 and 8.0 per 100 patient‐years of exposure with IDegLira and placebo, respectively, without obvious patterns in the type of events. Conclusions: IDegLira can be used in people uncontrolled with sulphonylurea ± metformin to improve efficacy with a safety profile in line with previous DUAL trials. What's new?: IDegLira is a combination of insulin degludec and liraglutide. Basal insulins and glucagon‐like peptide‐1 (GLP‐1) receptor agonists have complementary effects in a Type 2 diabetes treatment regimen, with GLP‐1 receptor agonists also being insulin‐sparing. Treatment guidelines often advocate discontinuing sulphonylureas on basal insulin initiation, but widespread concomitant use of these drugs continues in current clinical practice. It is therefore anticipated that many sulphonylurea‐treated people will have IDegLira added to their therapy, yet this combination has not previously been studied This randomized controlled trial shows that IDegLira can be used in people uncontrolled with sulphonylureas ± metformin to improve efficacy with a favourable benefit–risk profile.